The use of filtered gray water in family farming drip systems (Research, Society and Development, 2020)
The demand for water has led small farmers to seek local solutions to increase the supply of this input to crops, a fact that has driven the use of wastewater in rural communities in the semiarid region, with emphasis on the use of gray water. The present case study, which involves quantitative and qualitative investigations, sought to study the efficiency of the application of filtered gray water to from the evaluation and qualification of the use of pressurized systems and located in the conduction and distribution of this water in agroecosystems of family agricultural production. The work was carried out from August to December 2018 in rural communities of the cities of Ouricuri, Triunfo and Floresta in the State of Pernambuco. The data collected and analyzed about the performance of drip systems supplied with filtered gray water, within which flows offered, working pressure of the emitters, volumes of water produced and stored and its quality for irrigation, allowed to assess the technical performance of these systems with regard to distribution uniformity and water application efficiency. In this context it can be concluded that the low volume of grey water produced for pumping conditions farmers to adopt high watering shifts and application of low intensity water blades. A uniformity of distribution and the efficiency of water application, along the lines of the systems located in small areas, are classified from regular to good. The use of filtered grey water by families in their productive backyards contributes to significantly to decrease the random release of this effluent potentially environmental pollutant.